Development of WELIA (Website Linguistic Intelligence Assessment) for Class II Students of Elementary School - Otang Kurniaman; Eddy Noviana; Kurniawan Kurniawan; Eva Astuti Mulyani; Dede Permana; Intan Kartika Sari (Ta'dib, 2022)
The development of technology in the world of education is able to change technology-based education, thus the purpose of this research is to develop WELIA as an application that is able to measure the linguistic intelligence of students in elementary schools. The novelty in the research is designing WELIA (Website Linguistic Intelligence Assessment) which is used to assess or measure the linguistic intelligence of elementary school students using technology. The results showed that the average score of 3 practitioner validators on 11 components showed a figure of 81.81% - 93.18% with a very decent category level. The first practitioner validator gave an assessment with a very feasible category of 11 assessment components, so that a percentage value of 81.81% was obtained for media assessment. Expert validators on 11 components showed a score of 84.09% - 88.63% with a very feasible category level. The first expert validator gave an assessment with a very feasible category of 11 assessment components, so that a percentage value of 84.09% was obtained, it can be concluded that WELIA can be used to assess the linguistic intelligence of elementary school students.